Mutagenic efficiency of gamma rays on in-vitro regeneration in Indian mustard (Brassica juncea) - G, GARG; SONI, SHALINI; YADAV, SATISH KUMAR; KUMARI, POOJA (The Indian Journal of Agricultural Sciences, 2022)
In the study Indian mustard [Brassica juncea (L.) Czern. & Coss.] was treated with different doses (0, 2.5, 10, 20 and 100 Gy) of gamma rays (radioactive cobalt, 60Co) and the effects were investigated on callus initiation, seed germination, seedling growth, total chlorophyll, protein and proline contents of seedling leaves, which were grown from hypocotyl explant of non-irradiated and irradiated seeds. Experiment was conducted at School of Biotechnology, Gautam Buddha University during 2017–18. The results showed that irradiated seeds had increased seed germination per cent, seedling length, fresh and dry weight, total chlorophyll, protein and proline content in low dose exposure (2.5Gy). Callus cultures were established from hypocotyl explants of 15 days old seedlings obtained from irradiated and non-irradiated seeds of B. juncea on MS1 [MS+BAP (2 mg/ml) + 2,4 D (1 mg/ml)] and MS2 [MS+BAP (2 mg/ml) + 2,4 D (0.5 mg/ml)] medium. Cultured hypocotyls formed callus at their cut ends within a week and simultaneously differentiation started into nodular structures from their base. MS1 callus induction medium gave good callus induction percentage (58%) as compared to MS2. It was observed that the callus was green, compact and showed 83% induction frequency in 100Gy gamma dose in MS1, whereas in different dose treatment (2.5–20Gy), callus was white and friable. It turned light brown in 100Gy treatment in MS2 medium. Thus, results of the present study showed pre-sowing seed irradiation is an effective method of improving seed germination at the early developmental stage of the plant.